Keragaman Genetik dan Heritabilitas Beberapa Karakter Agronomi Populasi Galur F4 Padi Beras Hitam - Widyayanti, Setyorini; Basunanda, Panjisakti; Mitrowihardjo, Suyadi; Kristamtini, Kristamtini (Jurnal Penelitian Pertanian Tanaman Pangan, 2017)
The F4 black rice progenies and their two parents’ varieties were evaluated for their heritability and genetic variability at Padasan, Pakembinangun, Pakem, Sleman, Yogyakarta from May until September 2016. The purpose of this study is to determine genetic diversity, heritability estimates and genetic advance.The genetic materials used in this study consisted of 48 lines of F4 with their parents, local black rice and Situbagendit. The experiment was arranged in a randomized block designed with two replications. Seeds of each F4 progenies and their parents were sown 1 m × 2 m length of plot with 20 cm × 20 cm plant spacing. Genetic parameters estimatesd were calculated for heritability and genetic advance. Plant population of each F4 progenies and their parents were 40 plants in each replication.  The result showed that there were 11 progenies had an early day to maturity potential, 21 F4 progenies had a moderate plant height (60-95 cm), 13 progenies had a potential number of tillers per hill (10.26 to 18.76), 9 F4 progenies had a high number of filled grains per panicle (> 80% filled grains), and 7 F4 progenies had a potential of 1000-grain weight (g). Plant height had the highest coefficient of variability. Days to flowering, days to maturity, and pericarb color had the highest heritability estimates followed by plant height (70.6%). Plant height and pericarb color had the highest genetic advances, namely 21.7% and 49.2%, respectively. In relation to improve agronomic characters, plant height and pericarb color had a highest heritability and genetic advance also a wide genetic variability.